2021
DOI: 10.1016/j.trsl.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA profiles predict the severity of COVID-19 in hospitalized patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 47 publications
4
127
0
1
Order By: Relevance
“…In agreement with Garg et al, who investigated circulating microRNAs in critically ill COVID-19 patients, we discovered dysregulated miRNAs involved in inflammatory processes such as miR-21-5p and 126-5p [ 44 ]. In line with de Gonzalo-Calvo et al, who investigated the circulating miRNA profile in hospitalized patients admitted to clinical wards without requiring critical care and patients admitted to the intensive care unit (ICU), we found an upregulation of miR-27a-3p, miR-27b-3p, and miR-148a-5p that distinguished between ICU and ward patients [ 43 ]. Furthermore, like Donyavi et al we looked at cellular miRNAs in the acute and post-acute phase of COVID-19, we found miR-29a-3p and miR-146a-3p upregulated in our severe group of patients [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with Garg et al, who investigated circulating microRNAs in critically ill COVID-19 patients, we discovered dysregulated miRNAs involved in inflammatory processes such as miR-21-5p and 126-5p [ 44 ]. In line with de Gonzalo-Calvo et al, who investigated the circulating miRNA profile in hospitalized patients admitted to clinical wards without requiring critical care and patients admitted to the intensive care unit (ICU), we found an upregulation of miR-27a-3p, miR-27b-3p, and miR-148a-5p that distinguished between ICU and ward patients [ 43 ]. Furthermore, like Donyavi et al we looked at cellular miRNAs in the acute and post-acute phase of COVID-19, we found miR-29a-3p and miR-146a-3p upregulated in our severe group of patients [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, although there is very little or no literature about these miRNAs, they should be kept in mind as possible markers for progressive COVID-19 disease. Other miRNAs that were significantly deregulated in our analysis, such as miR-21-5p, miR-27, 126-5p, miR-146, or miR-142 have already attracted attention in other COVID-19 studies [ 42 , 43 , 44 ]. In agreement with Garg et al, who investigated circulating microRNAs in critically ill COVID-19 patients, we discovered dysregulated miRNAs involved in inflammatory processes such as miR-21-5p and 126-5p [ 44 ].…”
Section: Discussionmentioning
confidence: 87%
“…The profile of circulating miRNAs in hospitalized COVID-19 patients and the evaluation of their potential as biomarkers have also been studied by Gonzalo-Calvo et al [235]. Plasma miRNA profiling related to disease severity and mortality in ICU patients was performed using RT-qPCR.…”
Section: Sensitivity and Specificity Of Microrna Profiling In Covid-19 Patientsmentioning
confidence: 99%
“…The levels of those miRNAs were correlated with the duration of stay in the ICU. Therefore, plasma miRNAs might be considered new tools to help clinicians predict early deterioration in life among patients [235].…”
Section: Sensitivity and Specificity Of Microrna Profiling In Covid-19 Patientsmentioning
confidence: 99%
“…Recent research has suggested that a unique non-coding RNA signature can aid in identifying the likelihood of developing specific disease outcomes [2]. Alterations of miRNA levels in the blood have been described in multiple inflammatory and infectious diseases, including SARS-related coronaviruses [3][4][5][6][7][8][9]. MiRNAs are endogenous small non-coding RNAs, around 22 nucleotides, that bind specific messenger RNAs (mRNAs) through complementary base-pairing [10].…”
Section: Introductionmentioning
confidence: 99%